Nonlinear Association Between BMI and Depression Among Nonalcoholic Fatty Liver Disease: NHANES (2017–2018) - Hui Peng; Dan Zhou; Yuan Dai; Weifeng Chen (Behavioural Neurology)
Conclusion: There is a nonlinear relationship between BMI and depression among patients with NAFLD. BMI was positively related to depression when BMI is less than 29.8 kg/m2.